Spontaneous pregnancy in a patient with premature ovarian failure after ovarian platelet-rich plasma injection. Case report - Elizaveta E. Kraevaya; Natalia P. Makarova; Alina A. Babayan; Elena A. Kalinina (IP Berlin A.V., 2021)
The authors have described a clinical case of a spontaneous pregnancy in a patient with decreased ovarian reserve, secondary infertility and a history of an in vitro fertilization failure. Based on literature data and their own experience, the authors believe that intraovarian administration of platelet-rich plasma can increase the ovarian reserve and improve reproductive potential.